PROPOSAL OF MODIFICATION OF EUROCODE 2 IN TERMS OF CALCULATION OF THE PUNCHING SHEAR CAPACITY OF RC COLUMN FOOTINGS - Zoran Bonić; Elefterija Zlatanović; Nebojša Davidović; Nikola Romić; Nemanja Marinković (Facta Universitatis. Series: Architecture and Civil Engineering, 2021)
The paper first presents the calculation of the punching shear capacity of concentrically loaded reinforced concrete column footings according to the current Eurocode 2, which can be carried out in two ways: by conducting an iterative procedure and by a simplified procedure applying the diagrams. By using these procedures, the punching shear capacity calculation was performed for the footings examined within the experimental research of the authors of this study, as well as for the footings that were considered by experiments conducted by other authors. Based on the conducted analysis of the calculation results and experimentally recorded results, a modification of the expression of the current Eurocode 2 with regard to the calculation of the punching shear capacity of concentrically loaded RC column footings is proposed. The proposed modification more realistically takes into account the influence of compressive strength of concrete and the reinforcement ratio in the footing, so that its application provides the results of punching failure forces that are closer to the results recorded by experimental tests.